Efek Pergantian Air dengan Persentase yang Berbeda terhadap Tingkat Kelangsungan Hidup Larva Ikan Kakap Putih (Lates calcarifer) - Kevin Kevin; Muzahar; Wiwin Kusuma Atmaja Putra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2022)
This research was carried out on April - June 2021 at the Pengujan Fish Seed Center, Teluk Bintan Districts, Bintan Regency. The purpose of this study was to determine the best percentage of water change for the survival rate of barramundi larvae. This research was conducted using a Completely Randomized Design method (CRD) with 4 treatments and 3 replications consisting of: (1) K (without water change), (2) A (20% water change), (3) B (25% water change) and (4) C (30% water change). The results showed that the optimal percentages of water change was treatments A with a larval survival rate of 19,87Â±1,00% and a larval absolute length growth of 0,23Â±0,03 mm.